2013
DOI: 10.1523/jneurosci.4377-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Receptive-Field Subfields of V2 Neurons in Macaque Monkeys Are Adult-Like Near Birth

Abstract: Infant primates can discriminate texture-defined form despite their relatively low visual acuity. The neuronal mechanisms underlying this remarkable visual capacity of infants have not been studied in nonhuman primates. Since many V2 neurons in adult monkeys can extract the local features in complex stimuli that are required for form vision, we used two-dimensional dynamic noise stimuli and local spectral reverse correlation (LSRC) to measure whether the spatial map of receptive-field subfields in individual V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 37 publications
2
24
1
Order By: Relevance
“…However, it has been shown that the neural architecture necessary for binocular comparisons is present prenatally (Rakic, 1977) and neonatally (Horton & Hocking, 1996) in monkeys. Additional evidence suggests that some neurons in both V1 (Chino et al, 1997) and V2 (Maruko et al, 2008) in neonatal macaques respond to relative disparity, with sensitivity limited only by the spatial frequency tuning of the cell (Zhang et al, 2013). Thus, the present anatomical and physiological evidence supports disparity processing within the first weeks of life in macaque (thought to be roughly equivalent to the first two months of life in humans [Boothe, Dobson, & Teller, 1985]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that the neural architecture necessary for binocular comparisons is present prenatally (Rakic, 1977) and neonatally (Horton & Hocking, 1996) in monkeys. Additional evidence suggests that some neurons in both V1 (Chino et al, 1997) and V2 (Maruko et al, 2008) in neonatal macaques respond to relative disparity, with sensitivity limited only by the spatial frequency tuning of the cell (Zhang et al, 2013). Thus, the present anatomical and physiological evidence supports disparity processing within the first weeks of life in macaque (thought to be roughly equivalent to the first two months of life in humans [Boothe, Dobson, & Teller, 1985]).…”
Section: Discussionmentioning
confidence: 99%
“…Neurons responding preferentially to different amounts of disparity have been found in the cortex of newborn macaques (Chino, Smith, Hatta, & Cheng, 1997; Maruko et al, 2008; Zhang et al, 2013). Additionally, it has been proposed that the cortical architecture necessary to support disparity processing is present prenatally in monkeys (Horton & Hocking, 1996; Hubel & Wiesel, 1977; Rakic, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…Although they report that by 4 weeks of age the spatial receptive field structure in V2 is as complex as in adults (Zhang et al, 2013), but their ability to discriminate fine disparity differences was significantly reduced compared with adults (Maruko et al, 2008). V2 neurons of 8-week-old monkeys had significantly lower optimal temporal frequencies and resolutions than those of adults (Zheng et al, 2007).…”
Section: Neuronal Receptive Field Properties In Postnatal Developmentmentioning
confidence: 99%
“…The surgical preparation methods have been described elsewhere (Maruko et al, 2008;Tao et al, 2012;Zhang et al, 2013). Briefly, the animals were initially anesthetized with an intramuscular injection of ketamine hydrochloride (20-30 mg/kg) and acepromazine maleate (0.15-0.2 mg/kg).…”
Section: Surgical Preparationmentioning
confidence: 99%
“…In another 10 infants, we recorded from both V1 and V2. These infant ages were chosen based on our previous studies on the normal development of V1 and V2; 4 weeks of age is the youngest age when we could reliably analyze the receptive field properties of V1 and V2 neurons, and 8 weeks of age is the critical point of the postnatal development of neuronal development when neuronal responses become very similar to those in adults (Chino, Smith, Hatta, & Cheng, 1997;Maruko et al, 2008;Zhang et al, 2013;Zhang et al, 2005;Zheng et al, 2007).…”
Section: Oblique Effects In V1 and V2 Of Infant Monkeysmentioning
confidence: 99%